Review on Quantum Mechanically Guided Design of Ultra-Strong Metallic Glasses - Evertz, Simon; Schnabel, Volker; Köhler, Mathias; Kirchlechner, Ines; Kontis, Paraskevas; Chen, Yen-Ting; Soler, Rafael; Jaya, B. Nagamani; Kirchlechner, Christoph; Music, Denis; Gault, Baptiste; Schneider, Jochen M.; et al. (Frontiers in Materials, 2020)
Quantum mechanically guided materials design allows for the prediction of mechanical property trends and enables hence the identification of composition-structure-property relationships for crystalline materials. However, quantum mechanics based design guidelines and material selection criteria for ultra-strong metallic glasses have been lacking. Hence, based on an ab initio model for metallic glasses in conjunction with an experimental high-throughput methodology geared towards revealing the relationship between chemistry, topology and mechanical properties, we propose principles for the design of tough as well as stiff metallic glasses. The main design notion is that a low fraction of hybridized bonds compared to the overall bonding in a metallic glass can be used as a criterion for the identification of damage-tolerant metallic glass systems. To enhance the stiffness of metallic glasses, the bond energy density must be increased as the bond energy density is the origin of stiffness in metallic glasses. The thermal expansion, which is an important glass-forming identifier, can be predicted based on the Debye-Grüneisen model.